The Social Media Advertising and its Influence on Product Patronage in Ijebu-Ode, Ogun State, Nigeria - Odule, Kemi; Ogunye, Adeyinka (NIU Journal of Humanities, 2023)
This paper examines the Influence of Social Media advertising on product patronage in Ijebu-Ode, Ogun State. The aim is to measure the consumer’s acceptance of the platform in terms purchasing of goods and services. The study adopts the survey research method, and chiefly makes use of primary data, using the questionnaire as a research instrument for data collection. The data gathered and analyzed shows that contemporarily, the social media has advanced beyond chit-chat nature to business facilitation. Through the deployment of content analysis, the paper established that Facebook, and by extension social media, fosters an open, transparent environment where discussion flows freely between the consumer and the advertiser. It is however clear that a very thin line exists between these two groups on social media (Facebook) since the content of the sites are user-generated. Thus, anyone with a computer and Internet service can create and publish content, despite the challenges inherent in social media advertising. The paper concludes that consumers and the advertisers are gradually harnessing these new media platforms as part of their marketing strategies and others making buying decisions from them either on their own accord or through recommendations by others. Keywords: Social Media, Advertising, Product Patronage, Ijebu-Ode, Networking